Attrition of Nursing Professionals in Ghana: An Effect of Burnout on Intention to Quit - Douglas Aninng Opoku; Nana Kwame Ayisi-Boateng; Joseph Osarfo; Alhassan Sulemana; Aliyu Mohammed; Kathryn Spangenberg; Ali Baba Awini; Anthony Kwaku Edusei (Hindawi Limited, 2022)
Background. Burnout among nursing professionals at the workplace and how it influences their decision to quit the profession is crucial to the delivery of quality health service. The shortage of nursing professionals has serious consequences on the healthcare system. Aim. To examine the effect of burnout on intention to quit the profession among nursing professionals. Methods. A cross-sectional study among 375 randomly selected nursing professionals in active service at a tertiary healthcare setting in Kumasi, Ghana. The Maslach Burnout Inventory was used to determine burnout, and their intention to quit the profession was assessed by asking participants whether they ever thought about quitting the profession in the past 12 months. The effect of burnout on intention to quit was analyzed using logistic regression analysis. Results. The overall prevalence of burnout among participants was 2.1% (8/375) with 10.1% (38/375), 24.0% (90/375), and 56.3% (211/375) experiencing high emotional exhaustion, depersonalisation, and low personal accomplishment, respectively. Nearly half (49.3%, 185/375) of the participants had intention to quit the profession. Emotional exhaustion (adjusted odds tatio, AOR = 5.46; 95% CI = 2.25-13.20), depersonalisation (AOR = 1.77 95% CI = 1.07-2.95), and personal accomplishment (AOR = 2.27; 95% CI = 1.30-3.96) were associated with intention to quit the profession. Conclusion. Burnout has a negative effect causing intention to quit nursing profession. It is imperative to identify strategies such as occupational health surveillance that will aim at reducing the incidence of burnout at the workplace due to its consequences, one of them being the intention to quit.